Opportunities and challenges of algal fucoidan for diabetes management. (May 2021) - Wen, Yuxi; Gao, Luying; Zhou, Hengsheng; Ai, Chao; Huang, Xiaozhou; Wang, Mingfu; Zhang, Yuyu; Zhao, Chao
Abstract: Background: Diabetes mellitus is an endocrine and metabolic system disease characterized by hyperglycaemia and insulin resistance, and has become a prevalent disease around the world. Fucoidan has a good hypoglycaemic effect and ideal development potential in the treatment of diabetes based on their specific chemical structures, such as monosaccharide compositions and glycosidic linkages. Scope and approach: However, the relationship between structure-function and activity has not yet been clarified. This article discusses the structural characteristics of fucoidan, including its backbone structure, glycosidic bond positions, monosaccharide types, sulphate content, and molecular weight. The potential therapeutic effect of fucoidan on hyperglycaemia and diabetic complications caused by diabetes is also reviewed. Key findings and conclusions: Fucoidan reduces blood sugar levels through α-amylase and α-d -glucosidase inhibition, a Sirt-1-dependent manner, and the cAMP, PI3K/AKT, and JNK/AKT signalling pathways. The outstanding biological function of fucoidan is due its unique chemical structure. Among them, fucoidan of low molecular weight and high degree of sulfation displays greater anti-diabetic activity, and persulphated fucoidan derivatives showed significantly enhanced hypoglycaemic activities. Moreover, only (1, 3) and (1, 4) alternatively linked fucoidan showed a stronger inhibitory effect on α-d -glucosidase. Highlights: Low-molecular-weight and high sulphated fucoidan has high anti-diabetic activity. Mechanism between fucoidan and α-amylase and α-d -glucosidase has been studied. Fucoidan in regulating hyperglycaemia in a Sirt-1-dependent manner is presented.